A PATIENT WITH TICK-BORNE ENCEPHALITIS POLYNEURITISES FORM - Субботин, Анатолий Васильевич; Семенов, Владимир Александрович; Щербинина, Мария Сергеевна; Погодина, Ванда Вацлавовна; Смирнов, Вадим Дмитриевич; Бондаренко, Татьяна Евгеньевна (Medicine in Kuzbass, 2018)
The aim of this work is to study the rare clinical case of chronic tick-borne encephalitis (CHTBE), characterized by atypical course of infectious process, developing on intensive humoral immunity background.Materials and methods. The patient B., 50 years old, living in Kemerovo region, TBE endemic area. Was bitten by tick. The patient was twice vaccinated by: vaccine-TBE «EnceVir». The scheme of vaccination: between the first and second vaccinations – the interval is 16 days. Was hospitalized in the Kemerovo Regional Clinical Hospital with a diagnosis of Chronical form of TBE, mixed form (TBE and Ixodes tick-borne borreliosis). The immunological analysis was performed on TBE and ixodes tick-borne borreliosis was performed on ELISA assay.Results. The patient B, 50 years old serum was identified IgG antibodies, titer 1 : 1700 with a gradual decrease and stabilization from 1 : 800 to 1 : 600. IgM TBE antibodies were detected from the first days of the disease. TBE IgM were determined in titer from 1 : 600 to 1 : 3200 (5-fold increase of antibodies) in long-term observations. Throughout the infectious process, ixodes tick-borne borreliosis were not identified in the serum. In the neurological status was detected: a slight hypotrophy of the muscles of the first interdigital spaces, hypotrophy of shoulder girdle muscles, pain hypoesthesia at polyneuritis’s type. According to the results of the EMG study, the patient showed deceleration of excitation spread and neuropathy of the ulnar, median, peroneal and tibial nerves from both sides. According to MRI was detected the lack of accumulating contrast, presence of pathogenie pockets. The patient had no somatic symptoms of ixodes tick-borne borreliosis infection.Conclusion. The Diagnosis «Chronical TBE, polyneuritis form» based on the results of the EMG and ELISA studies in dynamic observations on the patient from 2016-2017.
Keywords: chronic tick-borne encephalitis; polyneuritis form; humoral immunity